Measuring Anchoring Bias among University Students - Majeed, Azhar Mohammed; Ahmed, Maryam Alaa (Journal of Cultural Analysis and Social Change, 2025)
Anchoring bias, first identified by Tversky and Kahneman, is a cognitive phenomenon whereby individuals’ judgments are influenced by incidental numerical values, with initial reference points (anchors) disproportionately affecting subsequent evaluations. This study aimed to measure anchoring bias among university students and examine differences based on gender and academic specialization. A total of 400 students from the University of Baghdad, equally divided by gender and academic discipline (humanities and sciences), participated. An 18-item anchoring bias scale was developed, validated through expert review, and tested for reliability using split-half (r = 0.75) and test–retest (r = 0.73) methods. Results indicated that the sample exhibited anchoring bias. Statistically significant differences were observed according to gender, favoring females, and academic specialization, favoring students in the humanities. These findings suggest that cognitive heuristics such as anchoring influence judgment among university students and that demographic factors can moderate the extent of this bias.